A CASE OF PUGHEADEDNESS IN THE CROAKER JOllNIUS ANEUS FROM KHOR AL-ZUBAIR, NORTHWEST OF THE ARAB GULF, BASRAH, IRAQ - Hassan, LAJ Al; Naama, A K (Indian Journal of Fisheries, 2011)
A CASE OF PUGHEADEDNESS IN THE CROAKER JOllNIUS ANEUS FROM KHOR AL-ZUBAIR, NORTHWEST OF THE ARAB GULF, BASRAH, IRAQ